2021
DOI: 10.3389/fncel.2021.636176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Estrogen and Estrogen-Like Molecules in Neurogenesis and Neurodegeneration: Beneficial or Harmful?

Abstract: Estrogens and estrogen-like molecules can modify the biology of several cell types. Estrogen receptors alpha (ERα) and beta (ERβ) belong to the so-called classical family of estrogen receptors, while the G protein-coupled estrogen receptor 1 (GPER-1) represents a non-classical estrogen receptor mainly located in the plasma membrane. As estrogen receptors are ubiquitously distributed, they can modulate cell proliferation, differentiation, and survival in several tissues and organs, including the central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 217 publications
(325 reference statements)
1
77
0
2
Order By: Relevance
“…Recently encouraging clinical results with a combination of herbs have shown to be effective and safe in decreasing menopause symptoms (Rattanatantikul et al, 2020). Also, phytoestrogens and their metabolites from medicinal plants have been shown to mimic the benefits of endogenous estrogens, and estrogen-based therapies are considered promising approaches for preventing the onset and progression of neurodegenerative disorders (Bustamante-Barrientos et al, 2021). Though, xenoestrogens derived from plastic polycarbonates, such as water bottles and varnish coating in food cans, can alter estrogen-mediated signaling pathways inducing a negative effect on health.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Recently encouraging clinical results with a combination of herbs have shown to be effective and safe in decreasing menopause symptoms (Rattanatantikul et al, 2020). Also, phytoestrogens and their metabolites from medicinal plants have been shown to mimic the benefits of endogenous estrogens, and estrogen-based therapies are considered promising approaches for preventing the onset and progression of neurodegenerative disorders (Bustamante-Barrientos et al, 2021). Though, xenoestrogens derived from plastic polycarbonates, such as water bottles and varnish coating in food cans, can alter estrogen-mediated signaling pathways inducing a negative effect on health.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…88,89 It has been reported that estradiol boosts neurogenesis correlating with cognitive improvement. 90,91 Moreover, estradiol can also ameliorate the neurodegenerative processes of Alzheimer's and Parkinson's diseases. 91,92 It is noteworthy that the phytoestrogen 8-PN, with estradiol-like effects, exhibits an exceptional activity in binding to the a-estrogen receptor.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 Moreover, estradiol can also ameliorate the neurodegenerative processes of Alzheimer's and Parkinson's diseases. 91,92 It is noteworthy that the phytoestrogen 8-PN, with estradiol-like effects, exhibits an exceptional activity in binding to the a-estrogen receptor. 93 As well, 8-PN was reported to positively control GABA-induced responses and its potential in neurodifferentiating has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The health properties of phytoestrogens seem to go beyond their estrogen-like activity. Many studies have demonstrated that they, acting on other target molecules and signaling pathways, exert several health effects such as antiandrogenic properties, antioxidant action, cell cycle and differentiation inhibition, antiangiogenic properties, and modulation of the activity or expression of steroidogenic enzymes [310] The antioxidant activity of genistein in in vitro and in vivo studies has been widely demonstrated. The results of clinical studies on genistein antioxidant activity evaluation have been clear, suggesting that this antioxidant activity could be the most reliable effect of this phytoestrogen.…”
Section: Discussionmentioning
confidence: 99%